Impact of PNPLA3 and IFNL3 polymorphisms on hepatic steatosis in Asian patients with chronic hepatitis C. - Chao-Min Huang; Kuo-Chin Chang; Chao-Hung Hung; King-Wah Chiu; Sheng-Nan Lu; Jing-Houng Wang; Chien-Hung Chen; Kwong-Ming Kee; Yuan-Hung Kuo; Ming-Chao Tsai; Po-Lin Tseng; Ming-Tsung Lin; et al. (PLoS ONE, 2017)
Background and aims A recent meta-analysis revealed that the genotype PNPLA3 rs738409 GG is associated with a higher risk of hepatic steatosis (HS) in Caucasian patients with chronic hepatitis C (CHC). However, controversial results were found regarding Asian populations. Furthermore, previous studies have shown a negative association between interferon lambda 3 (IFNL3) rs12979860 CC and HS in Caucasian CHC patients, but there have been no reports indicating any such association in Asian populations. In this study, then, we investigated the association of PNPLA3 and IFNL3 polymorphisms with HS in Asian CHC patients. Methods We enrolled consecutive CHC patients who underwent liver biopsy prior to antiviral therapy. We excluded those patients with decompensated liver disease, any co-existing chronic liver disease, or HIV or HBV co-infection. Results 1080 CHC patients were enrolled, and HS was found in 453 (41.9%) patients. The frequency distribution of the G allele was significantly associated with HS (P<0.001), and this conferred a higher risk to G allele homozygotes (OR: 2.06, 95% CI: 1.46-2.88, P <0.001) than to G allele carriers (OR: 1.98, 95% CI: 1.52-2.58, P<0.001). There was a borderline significant difference in the prevalence of HS in rs12979860 CC versus non-CC (40.8% versus 49.3%, P = 0.059). After adjustment for age, sex, body mass index, diabetes, and excessive alcohol intake, the rs738409 G allele homozygote carriers still carried a higher risk for HS (OR: 1.93, 95% CI: 1.35-2.77, P = 0.003). Conclusion The PNPLA3 rs738409 GG genotype is positively associated with HS, while the IFNL3 rs 12979860 CC genotype may be negatively associated with HS, in Asian CHC patients.